A review of bricks-and-clicks dual-channels literature: trends and opportunities. Issue 4 (1st December 2022) - Ozbilge, Armagan; Hassini, Elkafi; Parlar, Mahmut
Abstract: The proliferation of e-commerce has changed the retail market landscape significantly in most industries. Due to fiercer competition, many bricks-and-mortar retailers established an online channel and have become bricks-and-clicks. On the other hand, some e-tailers are adding a conventional channel to their portfolio by launching physical stores or forming a partnership with traditional retailers. Deciding on whether or not to adopt a dual-channel policy and how to operate it, in the presence of online sales, present multiple and unique research challenges. More than two decades of research have accumulated and there is a need for a comprehensive look at what has been achieved and where more research is required. Recent reviews in the field are limited in scope and depth: they focus on fulfillment and distribution issues only and cover a limited portion of the literature, less than 60 journal papers versus more than 260 papers in this survey. In this paper, we offer a structured literature review (SLR) on bricks-and-clicks dual-channels. We contribute to the literature in three main areas: (1) We present a comprehensive look at all operational aspects of bricks-and-clicks dual supply chains, (2) provide a systematic discussion of common demand modeling functions, and (3) analyze the reviewed literature, identify recent research trends and opportunities, and illustrate how existing research can be used to address up-to-date challenges in the industry.